¿qué piensan los estudiantes de medicina veterinaria y de zootecnia sobre desarrollo rural? (2006)
The educational institutions and their members have a particular perception about rural development. This vision can be conditioned by personal experience and by the education that is offered. This article surveyed the concept of rural development of the students of the school of Veterinary Medicine and Zootecnia of the National University of Colombia. The information obtained showed a particular vision from the young people about rural development. The ideas of students were evaluated at different moments of its formative process, comparing aspects like perception on rural development, ways of reaching it and about who should lead the process. Equally to evaluate the perception about the possibility of reaching or not the development of the sector in a certain period of time.